Condition monitoring of train door systems - Muhammad Abbas Mahat (2019)
This paper discusses further implementation of a previously developed condition monitoring system. This involves physically sizing down previous works, simplification of the data retrieval process from multiple monitoring systems via Wi-Fi and identifying the level of need for maintenance on the train door.